Dominican Republic : Request for Purchase under the Rapid Financing Instrument-Press Release; Staff Report; and Statement by the Executive Director for the Dominican Republic. (IMF Staff Country Reports; Country Report ;, 2020)
This paper analyzes Dominican Republic's Request for Purchase Under the Rapid Financing Instrument (RFI). The RFI provides timely resources to the authorities which they intend to mobilize for essential coronavirus disease 2019 (COVID-19)-related health expenditure and support to the vulnerable population. The pandemic has significantly weakened the Dominican Republic's macroeconomic outlook for 2020 and created financing needs that require additional support. The authorities are also seeking support from other multilateral institutions. Macroeconomic and financial policies have been accommodative in response to the pandemic. The temporary fiscal measures to accommodate higher public healthcare spending and targeted transfers to the most vulnerable are appropriate. The IMF emergency assistance under the RFI is expected to help provide the much-needed resources to address the urgent balance of payments needs and support essential COVID-19-related health expenditure. The support of other international financial institutions and development partners would be crucial to close the remaining financing gaps, ease the adjustment burden, and preserve the Dominican Republic's dynamic economic growth.